Feasibility and Safety of Sac Embolization Using N-Butyl Cyanoacrylate in Emergency Endovascular Aneurysm Repair for Ruptured Abdominal Aortic Aneurysms or Isolated Iliac Artery Aneurysms. (October 2020) - Ohba, Shota; Shimohira, Masashi; Hashizume, Takuya; Muto, Masahiro; Ohta, Kengo; Sawada, Yusuke; Mizuno, Akihiro; Nakai, Yosuke; Suda, Hisao; Shibamoto, Yuta
Purpose: To evaluate the feasibility and safety of sac embolization with N-butyl cyanoacrylate (NBCA) in emergency endovascular aneurysm repair (EVAR) for ruptured abdominal aortic aneurysm (AAA) and iliac artery aneurysm (IAA) in comparison to EVAR without sac embolization. Materials and Methods: Between February 2012 and December 2019, among 44 consecutive patients with ruptured AAA or IAA, 29 underwent EVAR. Of these, 22 patients (median age 77.5 years; 18 men) had concomitant sac embolization using NBCA; the remaining 7 patients (median age 88 years; 6 men) underwent EVAR without sac embolization and form the control group. The technical success, clinical success (hemodynamic stabilization), procedure-related complications, and mortality were compared between the groups. Results: All EVAR procedures and embolizations were successful. The clinical success rates in the NBCA and control groups were 95% (21/22) and 71% (5/7), respectively (p=0.14). There was no complication related to the procedure. Type II endoleak occurred in 4 of 21 patients (19%) in the NBCA group vs none of the control patients. One patient (5%) died in the NBCA group vs 3 (43%) in the controls (p=0.034). Conclusion: Sac embolization using NBCA in emergency EVAR appears to be feasible and safe for ruptured AAA and IAA.